Digital Green Laws: The Role of Legal Norms in Advancing Climate Technology for Sustainable Development - Deni Yusup Permana; Stefan Mihaila; Radu Popa (Yayasan Adra Karima Hubbi, 2025)
Background. The intersection of environmental governance and digital innovation has introduced new opportunities for addressing climate change through technology-driven solutions. However, the role of legal norms in facilitating or hindering the development and deployment of climate technologies remains underexplored. Purpose. This study investigates how legal frameworks can effectively support digital green technologies such as AI-based environmental monitoring, blockchain for carbon tracking, and smart infrastructure for renewable energy as tools for achieving sustainable development goals. Method. The research aims to examine the normative gaps, institutional barriers, and regulatory innovations needed to align legal systems with emerging climate technologies. Employing a normative-legal research design combined with comparative policy analysis, the study evaluates legal instruments from the European Union, Singapore, and selected developing countries. Results. The findings indicate that while some jurisdictions have begun to integrate digital green laws into their climate strategies, others lag due to regulatory fragmentation, data governance challenges, and insufficient legal innovation. Conclusion. The study concludes that adaptive, principle-based legal frameworks are essential to accelerate climate tech deployment while ensuring transparency, equity, and sustainability. A proactive legal architecture is critical for steering climate technology toward inclusive and effective environmental governance.